Analisis Numerik Pengaruh Gasket pada Windshield Pesawat Komuter 19 Penumpang Terhadap Fenomena Bird Strike - Laksono, Agung; Sitompul, Sahril Afandi; Suprianto, Agus; Fitriansyah, Rizky (FTK UNSURYA, 2022)
Aircraft are currently quite popular transportation, due to its ability to utilize air space as a flight path, so that it can be efficient in mileage. To support the safety of airplane passengers, every component on the aircraft must pass the test. One of them in the aircraft windshields that are prone to collisions with other objects. In accordance with the regulations in the Civil Aviation Safety Regulation (CASR) the windshield must withstand the impact load of a 0,91 kg bird. In this simulation, the material shape of the bird uses the EOS Tabular type. For modeling windshields, frame¸ gaskets and birds use a general method for solid materials, namely the Lagrangian method. Rubber used as gasket material with mooney rivlin for modeling material behavior. the polymethyl methacrylate and aluminum alloy 7075 T6 material is used in the windshield and frame. Numerical modeling is validated using analytical results. The gasket thickness of 2 mm produces the most optimum energy absorption. The use of gaskets on the windshield does not have a significant effect on the windshield because the gasket on average is only able to absorb 5% of the total energy absorbed by all windshield parts. The collision parameter that produces the greatest failure occurs at a speed of 87,5 m/s with -15o angle. The area that is most prone to material failure is in the area of the upper bolt hole.